Critérios de identificação e controle das normas tributárias extrafiscais - Detzel, Aline Martinez Hinterlang de Barros (2018)
It is an incontrovertible fact that extrafiscality, a legal instrument legitimized for the purpose of pursuing certain constitutionally defined goals, has grown exponentially. The common option of the competent agents regarding the use of this legal instrument demands a deeper analysis on the structuring aspects of extra-fiscal tax. In this context, the identification of possible structuring rules of extra-fiscal tax becomes urgent, thus facilitating the application of certain legal control mechanisms. The theme of extrafiscality, as presented in this study, demands the overcoming of some of the positions adopted by Brazilian tax doctrine. With this, it is intended to add to the topic legal aspects of great importance to the Tax Law, which contribute to the structuring and maintenance of a more efficient and secure constitutional tax system, from the point of view of the individual guarantees of the taxpayers